Existence and nonexistence of radial solutions of the dirichlet problem for a class of general k-Hessian equations - He, J.; Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong (2018)
In this paper, we establish the existence and nonexistence of radial solutions of the Dirichlet problem for a class of general k-Hessian equations in a ball. Under some suitable local growth conditions for nonlinearity, several new results are obtained by using the fixed point theorem.